The Transcription Factor bZIP60 Links the Unfolded Protein Response to the Heat Stress Response in Maize. Issue 11 (25th August 2020) - Li, Zhaoxia; Tang, Jie; Srivastava, Renu; Bassham, Diane C.; Howell, Stephen H.
Abstract : The transcription factor bZIP60 links a system that alerts plants to problems in protein folding to a system that protects plants from heat stress. Abstract: The unfolded protein response (UPR) and the heat shock response (HSR) are two evolutionarily conserved systems that protect plants from heat stress. The UPR and HSR occur in different cellular compartments and both responses are elicited by misfolded proteins that accumulate under adverse environmental conditions such as heat stress. While the UPR and HSR appear to operate independently, we have found a link between them in maize ( Zea mays ) involving the production of the BASIC LEUCINE ZIPPER60 (bZIP60) transcription factor, a pivotal response of the UPR to heat stress. Surprisingly, a mutant ( bzip60 - 2 ) knocking down bZIP60 expression blunted the HSR at elevated temperatures and prevented the normal upregulation of a group of heat shock protein genes in response to elevated temperature. The expression of a key HEAT SHOCK FACTOR TRANSCRIPTION FACTOR13 ( HSFTF13, a HEAT SHOCK FACTOR A6B [ HSFA6B ] family member) was compromised in bzip60 - 2, and the HSFTF13 promoter was shown to be a target of bZIP60 in maize protoplasts. In addition, the upregulation by heat of genes involved in chlorophyll catabolism and chloroplast protein turnover were subdued in bzip60 - 2, and these genes were also found to be targets of bZIP60. Thus, the UPR, an endoplasmic-reticulum–associated response, quite unexpectedly contributes to the nuclear/cytoplasmic HSR in maize.